Spy Thrillers - Bloom, Clive. author. aut Link
XI, 202 p.
Keywords: This volume presents 13 essays on the Spy Thriller in the 20th century and includes a critical introduction to the subject. Each essay combines historical and aesthetic theory with practical criticism. Authors covered range from Joseph Conrad and John Buchan to Ian Fleming and John Le Carre.